Regional Economic Outlook, April 2022, Sub-Saharan Africa. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2022)
The economic recovery in sub-Saharan Africa surprised on the upside in the second half of 2021, prompting a significant upward revision in last year's estimated growth. This year, however, that progress has been jeopardized. The Russian invasion of Ukraine has triggered a global economic shock that is hitting the region at a time when countries' policy space to respond to it is minimal to nonexistent. Most notably, surging oil and food prices are straining the external and fiscal balances of commodity-importing countries and have increased food security concerns in many countries. Moreover, the shock threatens to compound some of the region's most pressing policy challenges, including the COVID-19 pandemic's social and economic legacy, climate change, heightened security risks in the Sahel, and the ongoing tightening of monetary policy in the United States.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Foreign Exchange; International Agreements and Observance; International Economics; International Organizations